KOMPATIBILITAS CENDAWAN ENTOMOPATOGEN BEAUVERIA BASSIANA (BALS) VUILL (DEUTEROMYCOTINA: HYPHOMYCETES) DENGAN MINYAK SERAI WANGI - . Trizelia; Rusdi Rusli (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
Entomopathogenic fungi such as Beauveria bassiana are important natural control agents of many insects and can be potentially used as a bioinsecticide against several pests. Other potential source of bioinsecticide is certain plants such as fragrant lemongrass oil. The in vitro compatibility of the entomopathogenic fungus B. bassiana and fragrant lemongrass oil was evaluated. Fragrant lemongrass oil was tested in three different concentrations (0.1, 0.3 and 0.5%). Fragrant lemongrass oil was diluted in the steril SDAY medium at the different concentrations. Effects of these concentrations on conidia germination, colony growth and sporulation were compared. Fragrant lemongrass oil affected conidial germination, colony growth and sporulation of B. bassiana. Fragrant lemongrass oil was not compatible with the entomopathogenic fungus B. bassiana.